Hazardous drinking among young adults seeking outpatient mental health services. Issue 1 (December 2016) - Ordóñez, Anna; Ranney, Rachel; Schwartz, Maxine; Mathews, Carol; Satre, Derek
Abstract Background Alcohol use can have a significant negative impact on young adults in mental health treatment. This cross-sectional study examined prevalence and factors associated with hazardous drinking among young adults seeking outpatient mental health services, rate of alcohol use disorders (AUDs), and the relationship between hazardous drinking and other types of substance use. Methods Participants were 487 young adults ages 18–25 who completed self-administered computerized screening questions for alcohol and drug use. Alcohol use patterns were assessed and predictors of hazardous drinking (≥5 drinks on one or more occasions in the past year) were identified using logistic regression. Results Of the 487 participants, 79.8 % endorsed prior-year alcohol use, 52.3 % reported one or more episodes of hazardous drinking in the prior year and 8.2 % were diagnosed with an AUD. Rates of recent and lifetime alcohol, tobacco and marijuana use were significantly greater in those with prior-year hazardous drinking. In logistic regression, prior-year hazardous drinking was associated with lifetime marijuana use (OR 3.30, p < 0.001; 95 % CI 2.05, 5.28), lifetime tobacco use (OR 1.88, p = 0.004; 95 % CI 1.22, 2.90) and older age (OR 1.18 per year, p < 0.001; 95 % CI 1.08, 1.29). Conclusions In an outpatient mental health setting, high rates of hazardous drinking were identified, and drinking was associated with history of other substance use. Results highlight patient characteristics associated with hazardous drinking that mental health providers should be aware of in treating young adults, especially older age and greater use of tobacco and marijuana.